2004
DOI: 10.1002/app.13609
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Indian silk. I. Macrocharacterization and analysis of amino acid composition

Abstract: This first in a series of articles characterized the different varieties of Indian silk for their macrostructural parameters, such as filament length, degumming loss, denier, cross section, moisture regain, and intrinsic viscosity, for example. The results of amino acid analysis using a reverse-phase technique were also reported. Five Indian silk varieties-two mulberry (bivoltine and crossbreed) and three nonmulberry (tasar, muga, and eri)-were investigated. The differences existing between the different varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 10 publications
5
110
2
Order By: Relevance
“…The average weight of the cocoons used in this study was about 750 mg and cecropia cocoons with average weights of 800 mg-1 g were reported earlier [12]. Average cocoon weights of about 640 mg for mulberry silk, 3.4 g for A. mylitta, and 840 mg for P. ricini silks have been reported [2,3]. In another report, cocoon weights ranging from 7 to 14 g have been reported for A. mylitta cocoons [23].…”
Section: Properties Of the Cecropia Cocoonsmentioning
confidence: 49%
See 3 more Smart Citations
“…The average weight of the cocoons used in this study was about 750 mg and cecropia cocoons with average weights of 800 mg-1 g were reported earlier [12]. Average cocoon weights of about 640 mg for mulberry silk, 3.4 g for A. mylitta, and 840 mg for P. ricini silks have been reported [2,3]. In another report, cocoon weights ranging from 7 to 14 g have been reported for A. mylitta cocoons [23].…”
Section: Properties Of the Cecropia Cocoonsmentioning
confidence: 49%
“…The ratio of glycine/alanine for cecropia silk is 0.54, much lower than that of 1.5 for mulberry and 0.8 for the common wild silks. The amount of glycine and alanine determines the crystallographic form of the proteins [2,3]. The lower ratio glycine/alanine in cecropia suggests that cecropia silk has a considerably different crystallographic structure compared to mulberry and wild silks.…”
Section: Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…A part from anti oxidant, these quercetins have anti-inflammatory, anti atherogenic, anti coagulation and anti hypertensive effects too. 24,25 These compounds also inhibit smooth muscle cells proliferation, migration and improve vascular function. Flavonoids reduce lipid peroxidation by scavenging ROS, chelation of transition metal ions along with reducing macrophage oxidative stress by inhibition of cellular oxygenases or by activating cellular antioxidants such as glutathione system.…”
Section: Safety Parametersmentioning
confidence: 99%